The Instructional Thematic Game for Children with Mild Mental Retardation: For Enhancement of Left-Right Recognition Skill - Dandhi Kuswardhana; Shinobu Hasegawa; Juhanaini Juhanaini (International Journal of Electrical and Computer Engineering (IJECE), 2017)
Children with mild mental retardation had several difficulties with interaction, remembering information, problem-solving, physic-motoric, learning problem, etc. Therefore, we proposed a novel framework to increase their learning skill using instructional thematic game rehabilitation framework based on Kinect sensor as the solution. Basically, the framework had three components. First, intellectual functions, which implied to the competencies reached through the game by the student. Second, instructional thematic game model, which was the concept to learn everything from the real single topic of the subject by associating to the abstract objects. Three, computer sensor device, which was the equipment as the bridge between the children and the program application. This research covered enhancement of right and left-hand recognition. We adopted Single Subject Research to evaluate the effectiveness of the system and to explore each of the individual’s progress. This process was divided into 2 steps. Namely, baseline stage and treatment stage. Apparently, from our finding, such framework gave the student an enhanced learning skill covering left-right recognition skill, decreasing the level of disturbance, and improving the level of learning independence.